1996
DOI: 10.1203/00006450-199608000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Interleukin (IL)-1β and IL-6 in Bronchoalveolar Lavage Fluid Obtained from Infants with Chronic Lung Disease of Prematurity

Abstract: Chronic lung disease (CLD) of prematurity is associated with an initial increase in pulmonary neutrophils followed by pulmonary fibrosis. We determined whether the proinflammatory cytokines, IL-1 beta and IL-6, were increased in the bronchoalveolar lavage fluid obtained from nine infants (median gestation 25 wk, birthweight 820 g) who developed CLD, seven (28 wk, 1110 g) who recovered from the respiratory distress syndrome (RDS), and four (38 wk, 2690 g) control infants. IL-1 beta and IL-6 protein were both in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
165
3
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(184 citation statements)
references
References 26 publications
14
165
3
2
Order By: Relevance
“…These include soluble intracellular adhesion molecule-1, IL-1b, IL-6 and IL-8. 17,19,20,[22][23][24][25][26]28 In contrast, conflicting results have been reported for VEGF 31,36 and endothelin-1 24,31 TA values in VPIs at risk of developing BPD. Thus, it is difficult to discern the clinical utility of such measurements of a majority of cytokines unless it has been consistently replicated in disparate populations, using standard definitions and techniques.…”
Section: Discussionmentioning
confidence: 99%
“…These include soluble intracellular adhesion molecule-1, IL-1b, IL-6 and IL-8. 17,19,20,[22][23][24][25][26]28 In contrast, conflicting results have been reported for VEGF 31,36 and endothelin-1 24,31 TA values in VPIs at risk of developing BPD. Thus, it is difficult to discern the clinical utility of such measurements of a majority of cytokines unless it has been consistently replicated in disparate populations, using standard definitions and techniques.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Since inflammation is a fundamental pathologic feature of CLD, the genetic variants of cytokine genes may be good candidates to explain some of the individual variation in the development of this complication. TNF-a is a central mediator in the inflammatory cascade and TA concentrations are elevated in infants who develop CLD.…”
Section: Discussionmentioning
confidence: 99%
“…Increased concentrations of inflammatory mediators in airway secretions during the first week of life have been associated with the development of CLD in the preterm infant suggesting that inflammation plays a central role in this condition. [1][2][3][4][5][6][7][8] Concentrations of tumor necrosis factor-a (TNF-a), a central mediator in the inflammatory cascade, are elevated during the first week of life in the tracheal aspirates (TA) obtained from infants who subsequently develop CLD. 1,2 The magnitude of TNF-a production may be in part genetically determined.…”
Section: Introductionmentioning
confidence: 99%
“…The persistence of inflammatory processes in the premature lung may lead to severe functional and structural changes resulting in the typical histological pattern of BPD as has been shown previously. 24,26,27 Inactivation of surfactant components, activation of elastase activity and impairment of alveolarization and vascularization are part of the initiated pathologic Association between MBL and pulmonary morbidity in preterms A Hilgendorff et al processes. [33][34][35][36][37] In line with our findings, Gibson et al 38 have shown previously an association between genetic polymorphisms in the MBL gene at codon 54 and the presence of long-term neurological outcome, that is, cerebral palsy in infants.…”
Section: Discussionmentioning
confidence: 99%
“…23 The persistence of inflammatory processes, partially triggered by early onset or nosocomial infections as well as ventilatorinduced lung injury, leads to impairment of alveolarization and vascularization. [24][25][26][27] Based on the fact that MBL concentrations in umbilical cord blood were found to be predictive for the development of infections in neonates and early childhood 11,28,29 and the knowledge that polymorphisms of the MBL gene profoundly influences levels of the protein, we hypothesized that genetic variation of the MBL gene could be associated with the clinical outcome of preterm infants o32 GA.…”
Section: Introductionmentioning
confidence: 99%